Aflatoxin exposure among young children in urban low-income areas of Nairobi and association with child growth - Kiarie, G.M.; Domínguez Salas, Paula; Kang'ethe, S.K.; Grace, Delia; Lindahl, Johanna F. (African Journal of Food, Agriculture, Nutrition and Development, 2016)
Populations in tropical and subtropical developing countries are exposed to largely uncontrolled levels of aflatoxins through food. These countries (especially in Africa and Asia) also present a high prevalence of stunting. Studies have reported an association between aflatoxin exposure and growth impairment in children but there is not yet conclusive evidence that aflatoxins are a significant cause of stunting in children, thus further research is warranted. In this cross-sectional study, 204 low-income households were randomly selected in two low-income areas of Nairobi, Kenya. Korogocho is a higher population density area and Dagoretti a lower population density area. We asked questions about household demographics and a 24-hour dietary recall was conducted in children aged 1–3 years. Child anthropometric measurements were also conducted. Height-for-age Z-scores (HAZ), weight-for-age Z-scores (WAZ) and weight-for-height Z-scores (WHZ) were calculated for each child using World Health Organization (WHO) growth standards reference data. Samples of foods were taken from the household or from the retailer for analysis using competitive enzyme-linked immunosorbent assay (ELISA). Laboratory results for aflatoxin levels in the food samples collected were used to calculate the daily aflatoxin intake, according to the results from the dietary assessment. The study found 41% of children sampled had stunted growth. Boys were more stunted than girls (p=0.057) and Korogocho had more stunted children than Dagoretti (p=0.041). In all, 98% of food samples collected tested positive for aflatoxin and there was an average exposure to aflatoxins of 21.3 ng/kg bodyweight per day. Exposure to aflatoxin M1 (AFM1), location and sex were significantly associated with HAZ, with boys and children from Korogocho having lower HAZ, and AFM1 was negatively associated with HAZ (p=0.047), indicating that AFM1 was associated with stunting. There was no association between total aflatoxins (aflatoxin B [AFB] and aflatoxin G [AFG]) and HAZ, WAZ and WHZ. The study showed a high prevalence of malnutrition, especially stunting, in two low-income urban sites, and this was most pronounced in the high-density area. The reported association between AFM1 and stunted children indicates that more research is needed on the health impacts of this aflatoxin in growing children.